Analisis Etika Antroposentrisme terhadap Krisis Ekologi Akibat Alih Fungsi Lahan Pariwisata: Studi Kasus di Desa Kuta - Afansyah Arrahman; Muhammad Sarjan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Anthropocentrism is an anthropocentric paradigm that positions human existence as the determining factor and central focus within the entire universal ecosystem. This perspective is based on the belief that the world was created solely for the benefit of humans. This study aims to analyze the influence of anthropocentric ethics on the ecological crisis triggered by land conversion for tourism in Kuta Village, Pujut District. This study employs a qualitative case study method with a descriptive-analytical approach based on field research supported by literature review. It explores how a perspective that places human interests at the center of nature influences physical development policies in tourist areas. The findings reveal that massive land conversion has caused significant environmental degradation, such as clean water crises and the loss of green spaces, as nature is viewed solely as an economic commodity. This analysis concludes that the ecological crisis in Kuta Village stems from the failure of an anthropocentric ethic in treating nature; therefore, a paradigm shift toward an ecosentric ethic is necessary—one that values ecosystem balance for the sake of future sustainability.